FRI0371 Autoimmune Diseases in Patients with Rheumatoid Arthritis. (9th June 2015) - Simon, T.A.; Kawabata, H.; Esdaile, J.M.; Moorthy, V.; Suissa, S.
Abstract : Background: RA is one of about 80 different types of autoimmune diseases. After cancer and heart disease, autoimmune diseases are the most common type of disease in the US, with an estimated prevalence of 3.2% and 5.9% in the US 1 and Europe, 2 respectively, depending on the source, with a corresponding increase in mortality. 3 Many autoimmune diseases share a common pathogenic mechanism, but there are few published studies quantifying the occurrence of other autoimmune diseases in patients with RA. Objectives: To estimate the prevalence of concomitant autoimmune diseases in an RA population and a matched osteoarthritis (OA) population. Methods: Using a US medical claims database, patients with RA or OA were identified in the MarketScan Commercial and Medicare Supplemental databases. Patients were required to have at least 180 days of continuous health plan enrolment before the qualifying RA or OA diagnosis between 1 January 2006 and 30 September 2013. For each of the RA cohort members, 5 age- and sex- frequency-matched OA patients were identified. Study index date corresponded to the first qualifying RA or OA diagnosis date during the study period. Prevalence rates and rate ratios with 95% CIs for the 28 prespecified autoimmune diseases during the 6-month period before the index date were computed, comparing the RA and OA cohorts. Results: A total of 200, 000 RA and 1 million age- and sex-matched OA patients were studied. The top ten most frequent autoimmune diseases measured by prevalence rate are presented (see Table ). Patients with RA were almost three times more likely to have at least one autoimmune disease in their history compared with patients with OA. In particular, patients with RA were 17.9 times more likely to have a concomitant diagnosis of psoriatic arthritis and more than 8.7 times more likely to have a concomitant diagnosis of lupus or Sjögren's syndrome than their age- and sex-matched OA counterparts. Conclusions: The presence of autoimmune diseases in patients with RA is much more frequent than in patients with OA. Our data suggest that the inter-relationship of RA with other autoimmune diseases, and the outcomes associated with the occurrence of multiple autoimmune diseases, may play an important role in treatment decisions and the understanding of autoimmune diseases as outcomes. References: Jacobson DL, et al. Clin Immunol Immunopathol 1997;84:223–43 Eaton WW, et al. J Autoimmun 2007;29:1–9 Walsh SJ, Rau LM. Am J Public Health 2000;90:1463–6 Disclosure of Interest: T. A. Simon Employee of: Bristol-Myers Squibb, H. Kawabata Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, J. M. Esdaile: None declared, V. Moorthy Consultant for: Bristol-Myers Squibb, S. Suissa Consultant for: Bristol-Myers Squibb, Genentech, Roche